An Experience Report on Teaching Scrum Principles in a Playful Way through Distant Collaboration with Online Whiteboards - Gama, Kiev; Oliveira, Higor (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
The COVID-19 pandemics forced classroom activities to be moved to an online setting. This sudden transition to emergency online teaching brought negative impacts to students worldwide, who had a significant decrease in aspects such as motivation, self-efficacy, and cognitive engagement. Social aspects were also affected due to a lack of classroom socialization, with almost no interaction with teachers or colleagues. Experimental approaches attempting to engage students have been explored to minimize these negative impacts. We report our experience of conducting an activity with that objective, involving two cohorts of students in their first semester of a Bachelor’s degree in Information Systems. They have never had any face-to-face contact and started their course under this emergency remote teaching format. We chose to use a playful approach to teach Scrum, an agile method of iterative and incremental product delivery that uses frequent feedback and collaborative decision making. Our goal was twofold: (1) teaching Scrum through a playful approach and (2) stimulating students to interact and socialize among themselves and with the teacher. Based on our previous classroom practice of adopting Lego4Scrum, a widespread method for Scrum training that uses LEGO®bricks, we adapted it to use an online whiteboard (Miro) with the support of a communication tool (Discord) for teams. We conducted pre- and post-activity surveys in combination with an open-ended questionnaire that helped us to have a snapshot of the students understanding of the main concepts presented in the activity. We also performed interviews with some students after the activity to understand their perception and the social impact it had.